Attenuation of Cadmium Toxicity by Methanol Extracts of Rauvolfia vomitoria and Aframomum melegueta leaves - Adeniyi, Temidayo; Akinpelu, Moronkeji; Akinlami, Omokehinde; Kolawole, Molade James; Oloye, Jesufemi; Akogun, Imoleayo (Folia Medica Indonesiana, 2024)
Highlights: 1. This study provides insight into the detrimental effect of cadmium exposure on mammalian cells using a murine model. 2. The co-administration of Rauvolfia vomitoria and Aframomum melegueta leaf extracts is more effective in ameliorating cadmium-induced toxicity than a single administration of each plant extract. 3. The co-administration of Rauvolfia vomitoria and Aframomum melegueta plant extracts can upregulate the expression of IL-10 and reverse the derangements in the TNF-α, IL-6, SOD, and GPX levels. Abstract Cadmium has long been known to be an environmental pollutant that can harm human health, with toxicity majorly affecting the kidneys and liver. This study aimed to investigate the mitigating potential of methanol extracts of Rauvolfia vomitoria and Aframomum melegueta leaves in cadmium-induced liver toxicity. Twenty-five male adult Wistar rats, averagely weighing 200 g, were randomly allocated into five groups, each comprising five rats. Group 1 was unexposed to any substances and only received distilled water. Group 2 was given cadmium at a standard dose of 12 mg/kg bw. Groups 3, 4, and 5 received 12 mg/kg bw of cadmium, and each group was treated with 200 mg/kg bw of Rauvolfia vomitoria leaf extract, Aframomum melegueta leaf extract, and a combination of both extracts, respectively. After 28 days, the animals were euthanized to obtain their livers, which were then excised and processed for histopathological, mRNA expression, and biochemical analyses. A one-way analysis of variance (ANOVA) was used to analyze the data, and Duncan multiple tests were employed to compare the categorical variables (p<0.05). The results revealed elevated levels of interleukin 10 (IL-10) in the rats treated with Rauvolfia vomitoria and Aframomum melegueta extracts when compared to Group 2. On the other hand, the treatment groups exhibited a significant decrease in tumor necrosis factor alpha (TNF-α) and interleukin 6 (IL-6) levels, along with significantly elevated levels of superoxide dismutase (SOD) and glutathione peroxidase (GPx). Group 5 showed a normal liver histoarchitecture similar to Group 1, reversing the histopathological abnormalities shown in Group 2. In conclusion, the co-administrative treatment using Rauvolfia vomitoria and Aframomum melegueta extracts reversed the cadmium-induced toxicity better than using each plant extract individually. This further suggests that Rauvolfia vomitoria and Aframomum melegueta leaf methanol extracts may ameliorate the effects of cadmium-induced toxicity, including reducing oxidative stress and fortifying the anti-oxidant system.